Erythema Annulare Centrifugum mimicking tinea corporis: A Case Report - Rahmadewi Rahmadewi; Riyana Noor Oktaviyanti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2019)
Background: Erythema annulare centrifugum (EAC) is a rare cutaneous disease characterized by erythematous and violaceous annular plaques that usually involved the thighs and the legs  with unknown etiology. EAC has a clinical similar to tinea corporis but different in terms of therapy. Case: A 52-year-old woman was complain redness patches on her both legs and abdomen since 2 month. Redness patches appeared suddenly. Firstly,  small patch like insect bite appeared  in her abdomen, but rapidly spread into her extremities especially at lower legs accompanied with itchy. She never complains about pain and burning sensation on his rash. No complain about ear, nose and throat disturbances, She has complain about toothache since 3 month ago. Physical examination showed on extremities inferior dextra and sinistra, there were erythematous macules sharply marginated that is varying in size. Regio abdomen and extremitas superior there were hyperpigmentasi macule sharply marginated that is varying in size. A potassium hydroxide microscopic, examination showed a negative result for a fungal infection. A skin biopsy was performed and the histologic examination revealed epidermis with spongiosis and in dermis with  infiltration hystiosit, eosinofil and lymphosit on capiler blood vessel. The clinical and histopathological features, with a supportive history of recurrent lesions, led to the diagnosis of EAC. We give patient with dexamethasone and cetirizine, the lesions regressed spontaneously 3 months after onset. Discussion: The main differential diagnosis in our patient include tinea corporis. Histopathology of the skin lesions was classical for EAC. EAC resolves either spontaneously or once the underlying disease has been successfully treated. Systemic glucocorticoids usually suppress EAC, but recurrence is common when these drugs are stopped.